Engineering a functional three-dimensional human cardiac tissue model for drug toxicity screening. (11th May 2017) - Lu, Hong Fang; Leong, Meng Fatt; Lim, Tze Chiun; Chua, Ying Ping; Lim, Jia Kai; Du, Chan; Wan, Andrew C A
Abstract: Cardiotoxicity is one of the major reasons for clinical drug attrition. In vitro tissue models that can provide efficient and accurate drug toxicity screening are highly desired for preclinical drug development and personalized therapy. Here, we report the fabrication and characterization of a human cardiac tissue model for high throughput drug toxicity studies. Cardiac tissues were fabricated via cellular self-assembly of human transgene-free induced pluripotent stem cells-derived cardiomyocytes in pre-fabricated polydimethylsiloxane molds. The formed tissue constructs expressed cardiomyocyte-specific proteins, exhibited robust production of extracellular matrix components such as laminin, collagen and fibronectin, aligned sarcomeric organization, and stable spontaneous contractions for up to 2 months. Functional characterization revealed that the cardiac cells cultured in 3D tissues exhibited higher contraction speed and rate, and displayed a significantly different drug response compared to cells cultured in age-matched 2D monolayer. A panel of clinically relevant compounds including antibiotic, antidiabetic and anticancer drugs were tested in this study. Compared to conventional viability assays, our functional contractility-based assays were more sensitive in predicting drug-induced cardiotoxic effects, demonstrating good concordance with clinical observations. Thus, our 3D cardiac tissue model shows great potential to be used for early safety evaluation in drug development and drug efficiency testing for personalized therapy.